Validation of the Capsule Endoscopy Crohn’s Disease Activity Index (CECDAI or Niv score): a multicenter prospective study - Niv, Y.; Ilani, S.; Levi, Z.; Hershkowitz, M.; Niv, E.; Fireman, Z.; O’Donnel, S.; O’Morain, C.; Eliakim, R.; Scapa, E.; Kalantzis, N.; Kalantzis, C.; Apostolopoulos, P.; Gal, E. (Endoscopy, 2012)
Background and study aims: The Capsule Endoscopy Crohn’s Disease Activity Index (CECDAI or Niv score) was devised to measure mucosal disease activity using video capsule endoscopy (VCE). The aim of the current study was to prospectively validate the use of the scoring system in daily practice.Methods: This was a multicenter, double-blind, prospective, controlled study of VCE videos from 62 consecutive patients with isolated small-bowel Crohn’s disease. The CECDAI was designed to evaluate three main parameters of Crohn’s disease: inflammation (A), extent of disease (B), and stricture (C), in both the proximal and distal segments of the small bowel. The final score was calculated by adding the two segmental scores: CECDAI = ([A1 × B1] + C1) + ([A2 × B2] + C2). Each examiner in every site interpreted 6 – 10 videos and calculated the CECDAI. The de-identified CD-ROMs were then coded and sent to the principal investigator for CECDAI calculation. Results: The cecum was reached in 72 % and 86 % of examinations, and proximal small-bowel involvement was found in 56 % and 62 % of the patients, according to the site investigators and principal investigator, respectively. Significant correlation was demonstrated between the calculation of the CECDAI by the individual site investigators and that performed by the principal investigator. Overall correlation between endoscopists from the different study centers was good, with r = 0.767 (range 0.717 – 0.985; Kappa 0.66; P < 0.001). There was no correlation between the CECDAI and the Crohn’s Disease Activity Index or the Inflammatory Bowel Disease Quality of Life Questionnaire or any of their components. Conclusion: A new scoring system of mucosal injury in Crohn’s disease of the small intestine, the CECDAI, was validated. Its use in controlled trials and/or regular follow-up of these patients is advocated.